Quantitative multiplex profiling of the complement system to diagnose complement‐mediated diseases. Issue 12 (9th December 2020) - Willems, Esther; Lorés‐Motta, Laura; Zanichelli, Andrea; Suffritti, Chiara; van der Flier, Michiel; van der Molen, Renate G; Langereis, Jeroen D; van Drongelen, Joris; van den Heuvel, Lambert P; Volokhina, Elena; van de Kar, Nicole CAJ; Keizer‐Garritsen, Jenneke; et al.
Abstract: Objectives: Complement deficiencies are difficult to diagnose because of the variability of symptoms and the complexity of the diagnostic process. Here, we applied a novel 'complementomics' approach to study the impact of various complement deficiencies on circulating complement levels. Methods: Using a quantitative multiplex mass spectrometry assay, we analysed 44 peptides to profile 34 complement proteins simultaneously in 40 healthy controls and 83 individuals with a diagnosed deficiency or a potential pathogenic variant in 14 different complement proteins. Results: Apart from confirming near or total absence of the respective protein in plasma of complement‐deficient patients, this mass spectrometry‐based profiling method led to the identification of additional deficiencies. In many cases, partial depletion of the pathway up‐ and/or downstream of the absent protein was measured. This was especially found in patients deficient for complement inhibitors, such as angioedema patients with a C1‐inhibitor deficiency. The added value of complementomics was shown in three patients with poorly defined complement deficiencies. Conclusion: Our study shows the potential clinical utility of profiling circulating complement proteins as a comprehensive read‐out of various complement deficiencies. Particularly, our approach provides insight into the intricate interplay between complement proteins due to functional coupling, which contributes to the better understanding of the various disease phenotypes and improvement of care for patients with complement‐mediated diseases. Abstract : In this study, we measured the 'complementome' of 83 individuals with various complement deficiencies by means of a quantitative multiplex mass spectrometry‐based assay. We found distinct profiles that provided better insight in the intricate interplay between complement proteins. The potential clinical utility of this approach was shown for three patients with poorly defined complement deficiencies.